Environmental Management Accounting: A Tool for Better Management Practice - Kassim, Che Ku Hisam Che Ku; Ariffin, Avylin Roziana Mohd; Muhmad, Siti Nasuha (Advances in Social Sciences Research Journal, 2024)
Over the years, there has been a growing emphasis among organisations on the need to address environmental issues and develop management practices and tools that are useful in improving environmental performance of the organisations. The deficiency of conventional accounting practices has spurred the infusion of environmental management accounting (EMA) and its adoption has been promoted at international, national and local government levels. The main purpose of this paper is to provide a general discussion on pertinent characteristics of EMA including its supporting tools to enhance its applicability and potential benefits that could be derived from its adoption. The discussion adds to the existing literature and provides a platform for future research intending to examine the extent of EMA development in an organisation.